STRATEGI PENANGANAN LALU LINTAS PADA KAWASAN CENTRAL BUSINESS DISTRICT (CBD) DI KOTA PEKANBARU BERDASARKAN PENDEKATAN TEKNIS - agru maulana (LPPM Universitas Abdurrab, 2021)
The problem of congestion in Indonesia is often resolved only by improving / supplying the road network through widening or adding roads. This is a practical strategy to respond to the demand for increased transportation, but this strategy is temporal in nature and actually encourages higher growth rates of motorized vehicles in cities. Traffic management is one of the traffic management strategies that make maximum use of existing transportation infrastructure and facilities. The Central Business District (CBD) or the City Center Region (DPK) is the center of all city activities and a strategic location for city-scale trading activities. One of the traffic problems in Pekanbaru City, especially the activity center area of ​​Jalan Jenderal Sudirman (in front of STC - Jalan Ir Juanda) is the poor performance level of the road both in terms of speed, traffic volume and also the density that occurs on the Jalan Jenderal Sudirman section. . From these problems, the problem solving is through traffic management by applying several scenarios using vissim, namely controlling street vendors, on street parking control, one-way / flow diversion systems and signalized intersection cycle arrangements. The most optimal scenario is to control the parking lot and change the parking angle of Jalan General Sudirman and Jalan Juanda to an angle of 300 and the application of Jalan M. Yamin into a one-way system to Jalan Sudirman and setting the cycle of signalized intersections so that the performance of the road is smaller at the level C (0.45-0.74).